Data base of Effect of aerobic exercise on cardiorespiratory capacity in survivors of covid-19: meta-analysis - Jiménez-Rodríguez, Hibsen Alonso (2023)
The purpose of this study was to quantify the effect size (TE) of aerobic exercise on cardiorespiratory capacity in survivors of the COVID-19 disease caused by the SARS-CoV 2 virus. Two data bases (EBNSCO host and PubMed) were reviewed over the months of August through November, 2021. A total 142 656 potential articles were reviewed and, after applying several filters, 9 studies that met the requirements for inclusion were included. The random effect model was used. A first meta-analysis that was biased (according to Egger test) obtained 12 TE. After identifying and eliminating groups with an extreme TE, a corrected, unbiased model was obtained with 7 studies and 9 TE was obtained, where it was found that aerobic exercise has a significant, positive and large-magnitude effect on the cardiorespiratory condition on survivors of the COVID-19 disease (TE = 0.849; IC95%: 0.715 – 0.9 82; Q = 7.13; p = 0.522; I2 = 0.87%; Egger p = 0.205). Interventions with aerobic exercise foster an improvement in cardiorespiratory capacity in patients who survived COVID-19. Two studies applied aerobic exercise only, whereas the other seven combined aerobic exercise with strength exercise and other modes. In all cases, a significant TE was obtained. Finally, these results were relatively homogeneous, with no evidence for the influence of possible moderating variables.